2013
DOI: 10.1123/ijsc.6.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Impression Management in Athletics: A Qualitative Study of How NCAA Division I Athletics Directors Understand Public Relations

Abstract: Intercollegiate athletics directors (ADs) in the United States are high-profile representatives of their departments and universities. Their publics include media, sponsors, donors, fans, faculty, students, and government officials. However, few studies have explored ADs from a public relations perspective, especially regarding their understandings of public relations. Therefore, the purpose of this study was to learn how ADs understand public relations in the context of their athletics departments. A phenomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Thus, PR and corporate communications must demonstrate value to CEOs in their strategic decisions (Steyn, 2012), beyond what CEOs view as traditional PR domains, to further their inclusion at the executive level (Neill, 2015). Pratt (2013) studied National Collegiate Athletic Association Division (NCAA) Division I athletic directors, whoin the intercollegiate contextwere the CEOs of their departments, with control over finances, structure, priorities, policies, and general management (Whisenant, Pedersen, & Obenour, 2002;Whisenant & Pedersen, 2004), Pratt (2013) sought to understand how they viewed and valued PR. She observed that they did not view PR as a separate, distinct entity or department, rather integrated into all parts of the athletic department that had contact with the public.…”
Section: Bridging Disciplines: the Strategic Communicative Organizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, PR and corporate communications must demonstrate value to CEOs in their strategic decisions (Steyn, 2012), beyond what CEOs view as traditional PR domains, to further their inclusion at the executive level (Neill, 2015). Pratt (2013) studied National Collegiate Athletic Association Division (NCAA) Division I athletic directors, whoin the intercollegiate contextwere the CEOs of their departments, with control over finances, structure, priorities, policies, and general management (Whisenant, Pedersen, & Obenour, 2002;Whisenant & Pedersen, 2004), Pratt (2013) sought to understand how they viewed and valued PR. She observed that they did not view PR as a separate, distinct entity or department, rather integrated into all parts of the athletic department that had contact with the public.…”
Section: Bridging Disciplines: the Strategic Communicative Organizationmentioning
confidence: 99%
“…This aspect is believed to confer competitive advantage to achieve success. These characteristics are influenced by external publics of the athletic department and include sponsors, alumni, students, university management, and team fans themselves (Pratt, 2013) through organizational listening and the communication of those characteristics back to the external environment. These desired characteristics are also communicated to the organization to help ingrain these into organizational culture.…”
Section: Bridging Disciplines: the Strategic Communicative Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the history of sports media hints at the implied exchange between sports organizations and media by noting the implied exchange relationship that has existed between both sides: Organizations allow access to popular people (coaches and athletes) and events to provide valuable content, while the media provide free publicity to the organization (Holt, 2000; Holtzman, 1978; Menke, 1963; Woodward, 1949). In the particular context of American intercollegiate athletics, this exchange is operationalized across campus: As it is often phrased, sports is “the front porch of the university” (Pratt, 2013, p. 50).…”
mentioning
confidence: 99%
“…Outside of athletic pressures, institutional employees and the general public often coincide with the belief that intercollegiate athletics are the "front porch" of the university and its existence drives enrollment, branding, and more meaningful alumni relations. As a result, athletics are the first attribute of the university that the public often notices or what they are most familiar with concerning a given institution (Nixon, 2014;Pratt, 2013;Ridpath, 2010;Suggs, 2003). Another result is the perceived notion that having an NCAA Division I athletics department will result in economic benefit for the institution.…”
mentioning
confidence: 99%